2023
DOI: 10.3390/app13169126
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Auditory Training with an Open-Set Sentences-in-Babble-Noise

Abstract: Auditory training (AT) has limited generalization to non-trained stimuli. Therefore, in the current study, we tested the effect of stimuli similar to that used in daily life: sentences in background noise. The sample consisted of 15 Hebrew-speaking adults aged 61–88 years with bilateral hearing impairment who engaged in computerized auditory training at home four times per week over a two-month period. Significant improvements were observed in sentences comprehension (Hebrew AzBio (HeBio) sentences test) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The overall design of the current study follows that reported in [36]. Participants provided signed informed consent to participate in the study, answered a personal details questionnaire, and presented a hearing audiogram performed within the last six months to verify their hearing threshold and suitability for participation in the study.…”
Section: Overall Designmentioning
confidence: 99%
“…The overall design of the current study follows that reported in [36]. Participants provided signed informed consent to participate in the study, answered a personal details questionnaire, and presented a hearing audiogram performed within the last six months to verify their hearing threshold and suitability for participation in the study.…”
Section: Overall Designmentioning
confidence: 99%